Compras para la Salud: Aperitivos - Carley Rusch; Wendy J. Dahl (EDIS)
At first glance, you might think that snacking should be avoided because of the extra calories they can add to your diet. However, studies have shown there may be benefits when healthy snack choices are made. Read this article to learn about the benefits of healthy snacks and to learn healthy snack shopping tips. Includes recipes for homemade crispy kale chips and peanut butter and jelly yogurt. This 4-page fact sheet is the Spanish-langauge version of FSHN15-02/FS262: Shopping for Health: Snack Foods. Written by Carley Rusch and Wendy J. Dahl, and published by the Food Science and Human Nutrition Department, May 2016.